THE INFLUENCE OF COOPERATIVE SCRIPT METHOD ON THE ABILITY OF SUMMARY OF EXPLANATION TEXT - Ahmad Amarullah; Desri Arwen (STIBA IEC JAKARTA, 2022)
The purpose of this study was to analyze the differences in students' ability to write Explanatory Text The population in this study was class IX students of SMP Muhammadiyah 1 Tangerang City. Based on the results of the study, it can be concluded that the cooperative script method can streamline the learning outcomes of summarizing students' explanatory texts, it can be seen from the increased experimental class posttest. From the results of the t test, it shows that there is a difference between the results of the experimental class and the results of the control class. Based on the results of the posttest analysis using the t-test, it was found that tcount = 2.49 t table = 0.02 at a significant level. From the results of the pretest calculation, it is obtained that tcount = -5.10 ttable = 0.02, it can be concluded that Ho is rejected and H1 is accepted, it means that there is a significant difference in the class of students who learn to summarize explanatory texts that do not use the method and classes that learn to summarize explanatory texts that use the cooperative script method which get active. From the results of the post-test, it can be concluded that learning explanatory text using the cooperative script method further increases the success in summarizing the text. when learning to summarize explanatory texts, the experimental class students were more enthusiastic than those in the control class. Students easily think about what is found in the text and interact with each other. From the results of the post-test, it can be concluded that explanatory text learning by using the cooperative script method further increases the success in summarizing the text.